Climate-Based Suitability Assessment for Methane Mitigation by Water Saving Technology in Paddy Fields of the Central Plain of Thailand - Prangbang, Punyaporn; Yagi, Kazuyuki; Aunario, Jorrel Khalil S; Sander, Björn Ole; Wassmann, Reiner; Jäkel, Thomas; Buddaboon, Chitnucha; Chidthaisong, Amnat; Towprayoon, Sirintornthep (Frontiers Media, 2020)
The alternate wetting and drying (AWD) water management technique has been identified as one of the most promising options for mitigating methane (CH4) emissions from rice cultivation. By its nature, however, this option is limited only to paddy fields where farmers have sustained access to irrigation water. In addition, large amounts of rainfall often make it difficult to drain water from paddy fields. Therefore, it is necessary to understand the specific conditions and suitability of an area in which AWD is foreseen to be applied before its CH4 mitigation potential can be assessed in view of planning regional and national mitigation actions. In this study, we applied a methodology developed for assessing the climatic suitability of AWD to paddy fields in the central plain of Thailand in order to determine the potential spatial and temporal boundaries given by climatic and soil parameters that could impact on the applicability of AWD. Related to this, we also assessed the CH4 mitigation potential in the target provinces. Results showed that the entire area of the six target provinces was climatically suitable for AWD in both the major (wet) and second (dry) rice seasons. A sensitivity analysis accounting for uncertainties in soil percolation and suitability classification indicated that these settings did not affect the results of the suitability assessment, although they changed to some extent the distribution of moderate and high climatic suitability areas in the major rice season. Following the methodologies of the Intergovernmental Panel on Climate Change Guidelines, we estimated that the AWD scenario could reduce annual CH4 emissions by 32% compared with the emissions in the baseline (continuously flooded) scenario. The potential of AWD for annual CH4 emission reduction was estimated to be 57,600 t CH4 year−1, equivalent to 1.61 Mt CO2-eq year−1, in the target provinces. However, we recognize the possibility that other parameters not included in our current approach may significantly influence the suitability of AWD and thus propose areas for further improvement derived from these limitations. All in all, our results will be instrumental in guiding practitioners at all levels involved in water management for rice cultivation.